1972
DOI: 10.1159/000259375
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Fundamental Frequency of Polish Adult Males

Abstract: The purpose of this research was to study the speaking fundamental frequency (SFF) levels of young Polish males and compare them with similar populations of US males. To this end 103 Polish university students read a standard passage which was recorded and analyzed for SFF. The mean SFF level for this population was approximately 138 Hz, a value somewhat higher than that for 157 US male university students. Since there was also a size difference between the two populations, this factor was tested and found not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
1
3

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 0 publications
5
31
1
3
Order By: Relevance
“…In the absence of organic factors which could potentially be the source of such differences (e.g., body size or race-based vocal tract differences, Awan and Mueller, 1996), investigators have attributed cross-language differences to either linguistic or cultural factors, but there has been little attempt to characterize the phonetic basis of these differences (Deutsch et al, 2009) nor to question the suitability of the f0 measures used. For example, Majewski et al (1972) found higher mean f0 in young Polish males compared to previously reported values for American males. As they were unable to find a significant relation between mean f0 and body size of their subjects, they concluded that "possibly the differences between the two groups relate to crosscultural factors" (p. 119), but that "the reasons for such differences are not clear" (p. 124).…”
Section: Introductioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In the absence of organic factors which could potentially be the source of such differences (e.g., body size or race-based vocal tract differences, Awan and Mueller, 1996), investigators have attributed cross-language differences to either linguistic or cultural factors, but there has been little attempt to characterize the phonetic basis of these differences (Deutsch et al, 2009) nor to question the suitability of the f0 measures used. For example, Majewski et al (1972) found higher mean f0 in young Polish males compared to previously reported values for American males. As they were unable to find a significant relation between mean f0 and body size of their subjects, they concluded that "possibly the differences between the two groups relate to crosscultural factors" (p. 119), but that "the reasons for such differences are not clear" (p. 124).…”
Section: Introductioncontrasting
confidence: 61%
“…If these measures are capable of characterizing crossspeaker differences, and if some of them, at least, draw on language-specific intonational landmarks, then they may be well-placed for helping to understand the basis of crosslanguage differences in f0 range which have occasionally surfaced in the literature (e.g., Altenberg and Ferrand, 2006;Dolson, 1994;Hanley, Snidecor, and Ringel, 1967;Keating and Kuo, 2010;Majewski, Hollien, and Zalewski, 1972). In the absence of organic factors which could potentially be the source of such differences (e.g., body size or race-based vocal tract differences, Awan and Mueller, 1996), investigators have attributed cross-language differences to either linguistic or cultural factors, but there has been little attempt to characterize the phonetic basis of these differences (Deutsch et al, 2009) nor to question the suitability of the f0 measures used.…”
Section: Introductionmentioning
confidence: 99%
“…Touati (1993aTouati ( , 1993bTouati ( , 1995 : Registre -y étendue de fréquences utilisée Touati (1993a, 1993b) Dolbec et Fisher (1996 (1978), MAJEWSKI et al (1972) et KONZEL (1989), qu'elle n'influence pas directement la fréquence fondamentale de la voix parlée.…”
Section: Première Conception : Le Registre Comme Hauteur De La Voixunclassified
“…Le registre semble déterminé à la fois par la moyenne de fréquences et par la « ligne de base », ce qui permet de préciser la hauteur à laquelle se situe la voix d'un locuteur lors de la production d'un énoncé. Cette conception du registre comme hauteur est cependant associée à la notion complémentaire de « pitch range », ou étendue de fréquences, qui avait déjà été retenue par TOUATI dans des travaux antérieurs (TOUATI, 1991 On retrouve, dans cette troisième conception, le lien indissociable entre la hauteur et l'étendue mentionné par TOUATI (1993aTOUATI ( , 1993bTOUATI ( , 1995 (1978), MAJEWSKI et al (1972) et KONZEL (1989), qu'elle n'influence pas directement la fréquence fondamentale de la voix parlée.Le facteur de l'âge est aussi relié à la physiologie et peut alors avoir une influence sur le registre. Ces différences entrent directement en ligne de compte en raison de ce qui a été évoqué antérieurement, c'est-à-dire la taille de certaines composantes de l'appareil phonateur.…”
unclassified
“…However, taking male and female speech separately, a convincing absence of correlate has been obtained between overall pitch level and the speaker's body dimensions such as height, weight, size of larynx, and so on (Hollien and Jackson, 1973;Kunzel, 1989;Van Dommelen and Moxness, 1995;Collins, 2000;Gonzales, 2004;Lass and Brown, 1978;Majewski et al, 1972). In contrast, various studies have found that the pitch level of speech varies with the speaker's language (Hollien and Jackson, 1973;Majewski et al, 1972;Hanley et al, 1966;Yamazawa and Hollien, 1992), indicating that it is subject to a cultural influence (Dolson, 1994;Honorof and Whalen, 2005;Xue et al, 2002), though the precise nature of this influence has not received much consideration.…”
Section: Introductionmentioning
confidence: 99%